Examining politeness in the explanation of English and Tshivenda apologies and greetings - Nephawe, Farisani Thomas; Lambani, Matodzi Nancy (Technium Social Sciences Journal, 2022)
Proficiency in English politeness is an invaluable tool in maintaining effective communication. Differences in beliefs, culture and customs, values and norms exist between English and other languages. Non-native English speakers encounter difficulties when making apologies and greetings in the language. The research examined politeness of English and Tshivenda apologies and greetings. The research paper adopted a qualitative research approach designed to build a holistic narrative description concerning social or cultural phenomenon. Formal and informal interviews were carried out ethnographically to collect data from selected 15 historical experts at Phawe, Zoutpansberg in Limpopo Province, South Africa. Data were quantified, simplified, organised, and interpreted using an ’emic’ approach because they were interpreted from the perspective of the population under study. The research found that some Vhavenda people could narrate stories around politeness in their society. The research recommends the continuous practice of apologies and greetings to preserve the Vhavenda culture and custom.